Validasi E-Modul Microbes sebagai Sumber Belajar Digital dalam Pembelajaran Mikrobiologi - Vivi Fitriani; Mohamad Termizi Bin Borhan; Alene Binti Tawang (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to evaluate the validity of the Microbes E-Module as a digital learning resource for undergraduate microbiology education. The study employed a Research and Development (R&D) approach using the ADDIE model. The validation process was conducted during the Development phase and involved nine expert validators. The validated aspects included content, media, Project-Based Learning (PjBL), educational game components, and language. Data were collected using a validation questionnaire and analyzed descriptively using validity percentages. The results showed validity percentages of 99% for content, 94% for media, 96% for Project-Based Learning (PjBL), 95% for educational game components, and 98% for language. The overall validity percentage of the Microbes E-Module was 96%, indicating that it met the criteria of very valid. These findings provide evidence that the Microbes E-Module has achieved a very high level of validity based on expert evaluation across all validated aspects. Further studies are recommended to investigate the module's practicality and effectiveness during the Implementation and Evaluation phases of the ADDIE model.